1984
DOI: 10.1016/s0735-1097(84)80349-6
|View full text |Cite
|
Sign up to set email alerts
|

Differences in myocardial performance and load between patients with similar amounts of chronic aortic versus chronic mitral regurgitation

Abstract: It is not known if the favorable changes in preload and afterload that augment ejection performance in acute experimental aortic and mitral regurgitation are also present in patients with chronic regurgitation. Additionally, observations that patients with mitral versus aortic regurgitation respond differently to valve replacement suggest that differences exist preoperatively between these two types of volume overload. Therefore, ventricular mechanics were compared in nine patients with severe aortic regurgita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
73
1
1

Year Published

1988
1988
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(77 citation statements)
references
References 31 publications
2
73
1
1
Order By: Relevance
“…A major reason for such a lower complication rate is that LV size and EF improve after AVR. This improvement is in stark contrast to the situation with mitral regurgitation, 20 in which EF usually decreases after surgery, even after valve repair. 21,22 Conversely, with a similar volume overload, EF generally improves after AVR for AR, probably because of afterload reduction measured as systolic wall stress.…”
Section: Ar and Markedly Reduced Ef: Outcome Implicationscontrasting
confidence: 61%
See 1 more Smart Citation
“…A major reason for such a lower complication rate is that LV size and EF improve after AVR. This improvement is in stark contrast to the situation with mitral regurgitation, 20 in which EF usually decreases after surgery, even after valve repair. 21,22 Conversely, with a similar volume overload, EF generally improves after AVR for AR, probably because of afterload reduction measured as systolic wall stress.…”
Section: Ar and Markedly Reduced Ef: Outcome Implicationscontrasting
confidence: 61%
“…21,22 Conversely, with a similar volume overload, EF generally improves after AVR for AR, probably because of afterload reduction measured as systolic wall stress. 20 Therefore, patients with a low EF and markedly increased wall stress are likely to benefit from decrease in wall stress with notable EF increase (5 percentage points on average) after surgery. 15 Improvement in EF is not uniformly distributed, 23 and patients with depressed EF before surgery improve the most after surgery.…”
Section: Ar and Markedly Reduced Ef: Outcome Implicationsmentioning
confidence: 99%
“…[11][12][13]). The adequacy of the present computations can be partly verified with the measurement results from patients with AS and AR available in the literature [1][2][3][4][5][6][7][8][9].…”
Section: Introductionsupporting
confidence: 70%
“…In AR there is not only a volume overload but also an increase in the afterload and therefore of systolic wall stress. This distinguishes AR from mitral regurgitation [9], where a left ventricle volume overload is also present, but where the systolic wall stress is normal or even lower, since the regurgitant blood is ejected into the low pressure left atrium.…”
Section: Introductionmentioning
confidence: 99%
“…However, contractile function estimated as maxEN or EFc-end-systolic stress was frequently normal when the ejection fraction was preserved, which casts doubt on the concept that reduced afterload masks contractile dysfunction in chronic MR. Indeed, previous studies have also shown that afterload is normal or slightly increased in chronic MR,21 22 …”
Section: Discussionmentioning
confidence: 92%